Corrosion behaviors of super austenitic stainless steel weldment by GTAW welding for ships desulfurization system - Seo, Beomdeok; Kim, Yongseong; Oh, Seok; Lee, Seunghyo; Lee, Myeonghoon (Frontiers in Materials, 2023)
This study aims to clarify how filler-typed metals which were ERNiCrMo-3 and ERNiCrMo-4 affect corrosion resistance characteristics in the weldment of super austenitic stainless steel joints under the simulated desulfurization environment for ships. The desulfurization environment includes high temperature, chlorides, and acidic conditions, which, inevitably, can cause severe corrosion to great extent. For exact clarification, the variations of microstructure and the composition distribution in the weldment before and after welding was examined by using scanning electron microscope and energy dispersive X-ray spectroscopy. Then, the corrosion resistance characteristics were comparatively evaluated through the cyclic potentiodynamic polarization test together with potential measurement under the desulfurization simulated environments. In addition, the correlation between passive film and corrosion resistance characteristics was investigated after identifying the formed features of the passive film through the X-ray photoelectron spectroscopy analysis. Through these studies, it made certain, ERNiCrMo-4 filler metal with high Mo content is advantageous for the formation of MoO3 oxide on the surface, which belongs to form a stable passive film and maintains the corrosion resistance characteristics under the simulated desulfurization environment.